Problems Of The Maximum Limits Of Land Tenure In Indonesia - Amalul Arifin Slamet (Universitas Muhammadiyah Tangerang, 2022)
This article aims to examine the rules relating to the maximum limit of land tenure in Indonesia. In line with this, normative legal research was carried out on this issue. To find a bright spot, the legislation and expert perspectives are examined. So that it can be concluded that although there are rules that regulate the maximum limit of control of agricultural land, its implementation is still not optimal and cannot be carried out properly. Agricultural lands are currently not divided equitably, only piling up in certain communities who have access that allows them to own land with an area that exceeds the limit. And for building land, there are still no rules that clearly regulate the maximum limit except for residential land.Keywords: Maximum Limit, Land Tenure, Problems,